PERKEMBANGAN BAHASA DAN LITERASI ANAK USIA DINI - Aprilia, Cindy; Fasihah, Alya; Munawaroh, Hidayatu (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
This article discusses the importance of language development and literacy in early childhood as a foundation for communication and interaction skills in the future. The article examines factors that influence this development, both internal (cognitive, motor, and genetic abilities) and external (environment, media, and technology). The article emphasizes the crucial role of parents and educators in creating a conducive learning environment. Parents can provide appropriate stimulation through rich interactions, while educators can use engaging learning methods that are tailored to the child's development. Collaboration between the two is crucial for achieving optimal results. The article also highlights the importance of digital literacy in the digital technology era. The article uses a descriptive method to delve into in-depth information about language development and literacy in early childhood. Data was collected through direct observation, interviews, and documentary studies. The article concludes that language and literacy development in early childhood requires serious attention from parents, educators, and society. Through collective efforts, children can have a strong foundation in developing their language and literacy skills from a young age.